2022
DOI: 10.12669/pjms.38.4.5090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone mineral density in patients with gestational diabetes mellitus by ultrasonic bone mineral density measurement combined with Vitamin-D deficiency and analysis of influencing factors

Abstract: Objectives: To investigate the evaluation of bone mineral density (BMD) in patients with gestational diabetes mellitus (GDM) by ultrasonic bone mineral density measurement combined with Vitamin-D deficiency and its influencing factors. Methods: A total of 100 patients with gestational diabetes mellitus (GDM) admitted to our hospital from January 2017 to December 2020 were selected as the GDM group, and another 100 pregnant volunteers who underwent physical examination in our hospital were selected as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Driven by the increased resistance of insulin, estrogen, progesterone, and placental prolactin, the physiological and basic levels of plasma total cholesterol and triglyceride during pregnancy were increased to guarantee sufficient energy reserves (glucose, amino acids, and lipids) as well as full development and growth of the fetus ( 24 ). For the patients in the study group, the triglyceride level was 2.32 ± 0.94, which was higher than the normal level of puerpera and was consistent with the previous study results ( 25 28 ), but still at a normal level ( 29 ). Although a high triglyceride level significantly increased the risk of GDM as a risk factor for drug-resistant subtype of GDM ( 30 , 31 ), our study found that, for every 1-unit increase of triglyceride, the risk of anxiety disorder was reduced by 0.832 (95% CI, −1.653 to −0.011; P = 0.034), which was inconsistent with those in previous studies, suggesting that an appropriate increase in the blood lipid level had a protective effect on the anxiety for the patients.…”
Section: Discussionsupporting
confidence: 91%
“…Driven by the increased resistance of insulin, estrogen, progesterone, and placental prolactin, the physiological and basic levels of plasma total cholesterol and triglyceride during pregnancy were increased to guarantee sufficient energy reserves (glucose, amino acids, and lipids) as well as full development and growth of the fetus ( 24 ). For the patients in the study group, the triglyceride level was 2.32 ± 0.94, which was higher than the normal level of puerpera and was consistent with the previous study results ( 25 28 ), but still at a normal level ( 29 ). Although a high triglyceride level significantly increased the risk of GDM as a risk factor for drug-resistant subtype of GDM ( 30 , 31 ), our study found that, for every 1-unit increase of triglyceride, the risk of anxiety disorder was reduced by 0.832 (95% CI, −1.653 to −0.011; P = 0.034), which was inconsistent with those in previous studies, suggesting that an appropriate increase in the blood lipid level had a protective effect on the anxiety for the patients.…”
Section: Discussionsupporting
confidence: 91%
“…16,17 Previous studies have found that bone metabolism indexes can sensitively reflect the risk of osteoporosis, which are of high accuracy in predicting osteoporosis. 18 In this study, the analysis of the correlation between bone metabolism indexes, BMD and the progression of urinary protein in diabetic nephropathy shows that the three are closely related.…”
Section: Discussionmentioning
confidence: 69%
“…The findings indicated higher BMD loss in women with GDM compared to those without GDM. Additionally, Han et al [ 22 ] employed ultrasound bone densitometry in conjunction with vitamin D assessment to evaluate BMD in GDM patients. The study revealed lower BMD and 25-hydroxyvitamin levels in GDM patients compared to normal pregnant women.…”
Section: Discussionmentioning
confidence: 99%